2002
DOI: 10.1086/342698
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis Caused by Methicillin‐ResistantStaphylococcus aureus:Treatment Failure with Linezolid

Abstract: We describe 2 cases of endocarditis caused by methicillin-resistant Staphylococcus aureus that failed to respond to intravenous linezolid therapy but were successfully treated with trimethoprim-sulfamethoxazole plus gentamicin and vancomycin plus rifampin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 9 publications
1
42
0
2
Order By: Relevance
“…One study reported that vancomycin alone was more effective than either the combination of linezolid and vancomycin or linezolid alone for the treatment of MRSA endocarditis (18). Additionally, there have been several clinical reports of treatment failures (10,46,48). Our results are consistent with several published in vivo and in vitro studies suggesting that linezolid is bacteriostatic and may not be effective in patients with complicated sequestered infections such as infective endocarditis.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…One study reported that vancomycin alone was more effective than either the combination of linezolid and vancomycin or linezolid alone for the treatment of MRSA endocarditis (18). Additionally, there have been several clinical reports of treatment failures (10,46,48). Our results are consistent with several published in vivo and in vitro studies suggesting that linezolid is bacteriostatic and may not be effective in patients with complicated sequestered infections such as infective endocarditis.…”
supporting
confidence: 87%
“…Pharmacodynamic analysis. Two SEVs were removed from each model, for six simulated vegetations at 0, 4,8,24,32,48, and 72 h. The SEVs were homogenized and diluted in cold saline and plated onto TSA plates. The pH was monitored throughout all experiments with daptomycin due to the possible effects on its activity (37).…”
mentioning
confidence: 99%
“…The current study supports prior in vitro data by demonstrating that daptomycin decreases the bacterial load in vivo faster than comparator agents, including linezolid. Resistance to linezolid and persistent MRSA bacteremia during linezolid therapy have been reported (41,45). Furthermore, linezolid has been associated with myelosuppression, including neutropenia (16,19), which could exacerbate preexisting immunosuppression in special populations, including cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin is the treatment of choice for serious infections caused by oxacillin-resistant Staphylococcus aureus, and some isolates are reported that are susceptible only to this antibiotic (8,12). Oxacillin-resistant S. aureus isolates with reduced susceptibility to vancomycin (vancomycin intermediate-resistance S. aureus [VISA] isolates; the vancomycin MIC increases from 1 to 8 g/ml) have been recovered from patients receiving prolonged courses of vancomycin (1)(2)(3).…”
mentioning
confidence: 99%